La prediccion del calibre del corcho al final del turno y su aplicacion al muestreo de la produccion - Gonzalez Adrados, J.L.=700 1 Gonzalez Hernanadez, F.; Calvo Haro, R.
(Es, En)
ilus., 7 ref.
Keywords: QUERCUS SUBER; CORCHO; CLASIFICACION; PRODUCCION; ESPESOR; MUESTREO; ESPAÑA; ALCORNOQUE; CALIBRE